A bioconjugate vaccine against Brucella abortus produced by engineered Escherichia coli - Li, Shulei; Huang, Jing; Wang, Kangfeng; Liu, Yan; Guo, Yan; Li, Xiang; Wu, Jun; Sun, Peng; Wang, Yufei; Zhu, Li; Wang, Hengliang (Frontiers in Bioengineering and Biotechnology, 2023)
Brucellosis, mainly caused by Brucella, is a widespread zoonotic disease worldwide, with no available effective vaccine for human use. Recently, bioconjugate vaccines against Brucella have been prepared in Yersinia enterocolitica O:9 (YeO9), whose O-antigen structure is similar to that of Brucella abortus. However, the pathogenicity of YeO9 still hinders the large-scale production of these bioconjugate vaccines. Here, an attractive system for the preparation of bioconjugate vaccines against Brucella was established in engineered Escherichia coli. Briefly, the OPS gene cluster of YeO9 was modularized into five individual fragments and reassembled using synthetic biological methods through standardized interfaces, then introduced into E. coli. After confirming the synthesis of targeted antigenic polysaccharides, the exogenous protein glycosylation system (PglL system) was used to prepare the bioconjugate vaccines. A series of experiments were conducted to demonstrate that the bioconjugate vaccine could effectively evoke humoral immune responses and induce the production of specific antibodies against B. abortus A19 LPS. Furthermore, the bioconjugate vaccines provide protective roles in both lethal and non-lethal challenge of B. abortus A19 strain. Using the engineered E. coli as a safer chassis to prepare bioconjugate vaccines against B. abortus paves the way for future industrial applications.